FROM ANTI-ESTABLISHMENT POPULISM MOVEMENT TO POLITICAL PARTY: REVISITING UMMAT PARTY IN INDONESIA - Fairuz Arta Abhipraya; Fasih Raghib Gauhar; Ilham Agustian Candra (Jurnal Sosiologi Reflektif, 2023)
The rise of populist movements in Indonesia's political culture and democracy is influenced by the pragmatic ideologies of Muslim figures and perspectives that represent the majority group in the country. The formation of the Ummat Party represents one of the manifestations of the populist movement. The objective of this research is to elucidate the evolution of anti-establishment populist movements that have manifested as the Ummat Party, which has been initiated by Islamic populist figures in Indonesia, specifically Amien Rais. This study was conducted using a qualitative research method. Data collection techniques were carried out through observation and literature review. The findings revealed that Amien Rais employed anti-establishment populist narratives to create a movement of resistance, resulting in the establishment of the Ummat Party in Indonesia. By utilizing this narrative, the Ummat Party aims to challenge the socio-political status quo within Indonesia's democratic culture, advocating for change. Moreover, the Ummat Party exhibits a political agenda in utilizing the anti-establishment movement as a strategy to attain power and as a form of opposition against the current government in Indonesia.Gerakan populisme dalam budaya politik dan demokrasi di Indonesia banyak dipengaruhi oleh pemikiran praktis tokoh dan pandangan Muslim yang menjadi kelompok mayoritas di Indonesia. Munculnya Partai Ummat adalah salah satu dari bentuk gerakan populisme tersebut. Penelitian ini bertujuan untuk menjelaskan proses munculnya gerakan populisme anti-kemapanan yang bertransformasi menjadi Partai Ummat yang digagas oleh tokoh populis Islam di Indonesia, yakni Amien Rais. Penelitian ini dilakukan dengan menggunakan metode kualitatif. Teknik pengumpulan data dilakukan melalui observasi dan telaah pustaka. Hasil penelitian menunjukkan bahwa Amien Rais menggunakan narasi populis anti kemapanan guna membentuk gerakan perlawanan dengan mendirikan Partai Ummat di Indonesia. Melalui narasi ini pula, Partai Ummat berupaya untuk mengubah struktur sosial politik dalam budaya demokrasi di Indonesia. Lebih lanjut, terdapat kepentingan politik Partai Ummat untuk mengambil isu gerakan anti kemapanan ini sebagai sarana mencapai kekuasaan dan sebagai bentuk resistensi terhadap pemerintah Indonesia saat ini.